2017
DOI: 10.1007/s00403-017-1769-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-36 cytokines are increased in acne and hidradenitis suppurativa

Abstract: Interleukin (IL)-36 cytokines are new members of the IL-1 family, which include pro-inflammatory factors, IL-36α, IL-36β and IL-36γ, and a natural receptor antagonist IL-36Ra. Over recent years, much has been learned on their important functions in the regulation of immune response and, especially, on their role in many inflammatory skin diseases. However, to date, no data have been reported on their possible involvement in acne and hidradenitis suppurativa (HS). Here, we have shown that IL-36α, IL-36β, and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 28 publications
4
51
0
1
Order By: Relevance
“…The levels of IL‐36 family members in keratinocytes are markedly increased by many different stimuli, including Toll‐like receptor (TLR) agonists such as bacterial lipopolysaccharide . The mRNA expression of IL‐36α, IL‐36β and IL‐36γ was previously reported to be elevated in lesional skin of acne . Our study showed that the protein expression of IL‐36β, IL‐36γ and IL‐36Ra was increased in the epidermis and follicular epithelial cells in folliculitis and EPF compared with the levels in normal skin.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The levels of IL‐36 family members in keratinocytes are markedly increased by many different stimuli, including Toll‐like receptor (TLR) agonists such as bacterial lipopolysaccharide . The mRNA expression of IL‐36α, IL‐36β and IL‐36γ was previously reported to be elevated in lesional skin of acne . Our study showed that the protein expression of IL‐36β, IL‐36γ and IL‐36Ra was increased in the epidermis and follicular epithelial cells in folliculitis and EPF compared with the levels in normal skin.…”
Section: Discussionsupporting
confidence: 53%
“…7,8 The mRNA expression of IL-36a, IL-36b and IL-36c was previously reported to be elevated in lesional skin of acne. 14 Our study showed that the protein expression of IL-36b, IL-36c and IL-36Ra was increased in the epidermis and follicular epithelial cells in folliculitis and EPF compared with the levels in normal skin. IL-36 cytokines are secreted as precursor proteins with little or no bioactivity, so they require post-enzymatic processing to elicit their biological effects.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations